2006
DOI: 10.1042/bst0341199
|View full text |Cite
|
Sign up to set email alerts
|

Dwarfism and cytochrome P450-mediated C-6 oxidation of plant steroid hormones

Abstract: BRs (brassinosteroids) are plant steroid hormones that are essential for normal plant development. The dramatic dwarfism exhibited by mutants in the CYP (cytochrome P450) enzymes involved in BR biosynthesis indicates a role for these hormones in plant growth and development. Since the mid-1990s, collaborative research has been geared towards developing a better understanding of the CYP85 class of CYPs involved in BR biosynthesis in both Arabidopsis and tomato. Some of the most recent observations include the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…BL plays an important role in the development of reproductive organs in these species, whereas CS probably serves as a regulator of plant vegetative growth [ 51 ]. Although BL has already been reported in rice shoots [ 52 ], other authors showed that the step of BR biosynthesis involving the conversion of CS to BL does not seem to exist in rice [ 53 , 54 ]. The same situation seems to apply for other monocot grasses [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…BL plays an important role in the development of reproductive organs in these species, whereas CS probably serves as a regulator of plant vegetative growth [ 51 ]. Although BL has already been reported in rice shoots [ 52 ], other authors showed that the step of BR biosynthesis involving the conversion of CS to BL does not seem to exist in rice [ 53 , 54 ]. The same situation seems to apply for other monocot grasses [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Equally vague is whether hormone synthesis occurs in mature females versus embryos, if hormones are activated or inhibited by steroid dehydrogenase, and the cell processes influenced by hormones. Oxidized and reduced nicotinamide are likely to fluctuate in amount as metabolism changes during diapause, supplying triggers for modification of steroid dehydrogenase and cytochrome P450, an NADPH-requiring enzyme capable of irreversible steroid modification (Agarwal and Auchus, 2005;Lieberman et al, 2005;Bishop et al, 2006) and for which mRNA increases during Artemia diapause.…”
Section: Metabolismmentioning
confidence: 99%
“…Some differences notably exist among angiosperms for the end-products of BR biosynthesis. In Arabidopsis and tomato (Lycopersicon esculentum), these end-products are castasterone (CS) and BL, with BL being the more active of the two (Bishop et al, 2006). In contrast, it seems that rice plants do not produce BL, but use CS as bioactive BR instead (Yamamuro et al, 2000;Hong et al, 2005;Nakamura et al, 2006).…”
Section: Brassinosteroid Metabolism and Transport Pathways Br Occurrementioning
confidence: 99%